Household Overcrowding and Income Poverty: Insights from Poland - Dudek, Hanna (Przeludnienie a ubóstwo dochodowe gospodarstw domowych w Polsce: wyniki analizy, 2024)
The paper aims to assess the issues of overcrowding and income poverty in Poland and identify the socio-economic factors associated with these problems. To achieve these objectives, a multinomial logit model is applied to analyse data from the 2022 European Union Statistics on Income and Living Conditions (EU-SILC) survey. The study reveals that overcrowding and income poverty do not fully overlap. It identifies significant associations between these issues and factors such as the degree of urbanisation of the residence, the housing tenure status, the household type, and the educational level of its members. Moreover, it was found that households with disabled individuals, unemployed members, and households of two adults with three or more children are particularly vulnerable. These findings highlight the need for targeted policy measures to address different aspects of poverty.
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2024, Nr 22 (28), s. 21-30
Keywords: household; overcrowding; income poverty; EU-SILC; multinomial logit model; gospodarstwo domowe; przeludnienie; ubóstwo dochodowe; model logitowy dla wielu kategorii nieuporządkowanych